Research of implementation of the elearning to improve the learning in the figmmg - Calderón Celis, Marilú (2009)
This project is for the training of the University students of pregrado, maestrandos and Candidates for doctorate, with the modality e-Learning (Education distantly). In this first part of the project we have centred on the implementation of a virtual course of Pregrado’s Mining Metallic Analysis. The intention of estal offer answers to the need to propitiate a training to Post Grado’s level, in this context, we think that the modality distantly favors the implementation of offers towards the pedagogic innovation that the new technologies include to put them to the service of the process of education - learning. In this abstract we centre on the Implementation of the modality and Learning on platform windows that will serve us as model to realize it in Linux that still is not implemented in the FIGMMG and that has the purpose of avoiding the expense in licenses of software of Microsoft since this project this one protected in the Law Nº 28612 approved in the Congress of the Republic 23 of September of 2005 [12], that norm the use, acquisition of the Free Software in the public adminsitración. The present work has the purpose of Implementing the Modality and-Learning in the Faculty of Geological, Mining, Metallurgical and Geographical Engineering (FIGMMG) of the Universidad Nacional Mayor de San Marcos – Perú, to improve the learning of the University students.